Effectiveness of Intranasal Steroid Spray (Fluticasone Furoate) on Allergic Rhinitis: A Cross-sectional Study (Journal of Comilla Medical College Teachers' Association, 2024)
Background: Treatment for allergic rhinitis in addition to avoidance of allergens, involves various medications, including antihistamines, leukotriene receptor antagonists, and both topical and systemic corticosteroids. Fluticasone furoate is commonly used as a topical steroid, with intranasal steroid sprays are considered as the most effective option. However, there is a lack of established evidence regarding the effectiveness and safety of intranasal steroids.Objectives: The primary aim of the present study is to assess the efficacy of intranasal steroid spray (specifically, fluticasone furoate) in treating allergic rhinitis.Methods: In our study, we conducted a prospective cross-sectional investigation involving 155 patients with allergic rhinitis who visited the outpatient department of City Medical College Hospital. The selected patients were provided with a questionnaire to gather information concerning their symptoms, usage of intranasal steroids, and any related concerns.Results: All 155 patients completed the questionnaire. Among them, every patient utilized of intranasal steroid spray for the last one year. Our study reported that 82.58% patients are benefited by using intranasal steroid spray, 78.71% report better airway, and 76.77% observe a decrease in nasal discharge with multiple responses simultaneously. A total of 17.42% report no benefit at all, while 13.55% note a rebound effect, with 1.29% experiencing epistaxis.Conclusion: The practical effectiveness and occurrence of adverse events associated with intranasal steroid sprays closely mirror the findings observed in clinical trials. J Com Med Col Teachers Asso Jan 2024; 28(1): 24-26